Validation of a modified pre‐lysis sample preparation technique for flow cytometric minimal residual disease assessment in multiple myeloma, chronic lymphocytic leukemia, and B‐non Hodgkin lymphoma. Issue 5 (12th June 2020) - Bayly, Emma; Nguyen, Vuong; Binek, Adrian; Piggin, Anna; Baldwin, Kylie; Westerman, David; Came, Neil
Abstract: Background: Minimal residual disease (MRD) assessment of hematopoietic neoplasia below 10 −4 requires more leukocytes than is usually attainable by post‐lysis preparation. However, not all laboratories are resourced for consensus Euroflow pre‐lysis methodology. Our study aim was to validate a modified pre‐lysis protocol against our standard post‐lysis method for MRD detection of multiple myeloma (MM), chronic lymphocytic leukemia (CLL), and B‐non Hodgkin lymphoma (B‐NHL), to meet demand for deeper MRD assessment by flow cytometry. Method: Clinical samples for MRD assessment of MM, CLL, and B‐NHL (50, 30, and 30 cases, respectively) were prepared in parallel by pre and post‐lysis methods for the initial validation. Total leukocytes, MRD, and median fluorescence intensity of antigen expression were compared as measures of sensitivity and antigen stability. Lymphocyte and granulocyte composition were compared, assessing relative sample processing stability. Sensitivity of the pre‐lysis assay was monitored post validation for a further 18 months. Results: Pre‐lysis achieved at least 10 −4 sensitivity in 85% MM, 81% CLL, and 90% B‐NHL samples versus 24%, 48%, and 26% by post‐lysis, respectively, with stable antigen expression and leukocyte composition. Post validation over 18 months with technical expertise improving, pre‐lysis permitted 10 −5 MRD assessment in 69%, 86%, and 82% of the respective patient groups. Conclusion: This modified pre‐lysis procedure provides a sensitive, robust, time efficient, and relatively cost‐effective alternative for MRD testing by MFC at 10 −5, facilitating clinically meaningful deeper response assessment for MM, CLL, and B‐NHL. This method adaptation may facilitate more widespread adoption of highly sensitive flow cytometry‐based MRD assessment.